Mine Development and Operation (MDO) Planning Study of Temporary Ore Stockpile (TOS) at Laterite Nickel Mining Central Halmahera Regency North Maluku Province - Ayyub Abd. Hamid; Amrih Halil; Hilda Alakatiri (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Mine development and operation (MDO) is a construction process in the development and operation of mines to provide areas for the construction of facilities and infrastructure such as road construction, Temporary Ore Stockpile (TOS) sites, Permanent Ore Stockpile (POS) locations, etc. The purpose of this research is to manage the mine out area in the MDO TOS planning so that it can increase nickel production at the CUU site at PT. IWIP, which is located in Central Halmahera Regency, North Maluku Province. MDO TOS planning is carried out for 2 weeks. The basic design considerations refer to the data provided by the company, such as the MDO TOS area design, topographical survey, cut and fill, laminating. Processing of MDO TOS planning data in this study used Surpac Gemcom 6.3 software. From the results of data processing, the cut volume was 14,382 BCM, the fill volume was 8,599 BCM, and the laminating volume was 20,303 BCM.